Riparian restoration benefits across space and time in subtropical Australia: From drinking water quality to wider society - Joseph M. McMahon; James C.R. Smart; Ben Stewart-Koster; Syezlin Hasan; James S. Shortle; William N. Venables; Andrew Smolders; Morag Stewart; Don Butler; Jon M. Olley; David P. Hamilton; Stuart Bunn (Ecosystem Services, 2026)

Long-term variability of planetary boundary layer heights derived from radiosonde and flux tower observations in South Africa - Pfano M. Makhokha; Anzel De Lange; Liesl Dyson; Gregor Feig; Abri de Buys; Kathleen Smart (Atmospheric Research, 2026)

The isotopic composition of solid-phase extracted dissolved organic nitrogen in seawater - Yeongjun Ryu; Dario Marconi; Sandi M. Smart; Sarah E. Fawcett; Rodney Johnson; Run Zhang; Angela N. Knapp; Sergey Oleynik; Alfredo Martínez-García; Gerald H. Haug; Daniel M. Sigman (Marine Chemistry, 2026)

Extremely Low Sample Size Allows Age and Growth Estimation in a Rare and Threatened Shark - Peter M. Kyne; Jonathan J. Smart; Grant J. Johnson (Fishes, 2025)
Understanding life history parameters is key to assessing demography, biological productivity, and extinction risk of fishes. Age and growth analyses in chondrichthyan fishes (sharks, rays, and ghost sharks) is primarily undertaken through counting vertebral band pairs. For rare, threatened, and protected species such as river sharks (Carcharhinidae; Glyphis), obtaining sufficient vertebrae samples may not be possible. Here we use a very small sample size, selective size-class sampling, back-calculation techniques, and a Bayesian hierarchical model that accounts for repeated measures to provide age and growth information for the Speartooth Shark Glyphis glyphis from which comprehensive sampling is not possible. Ten individuals were selectively sampled from the Adelaide River, Northern Territory, Australia. Bayesian length-at-age models using a combination of informative and uninformative priors in a multi-model framework were applied to the observed and back-calculated data with the sexes combined. Band pair counts produced age estimates of 0–11 years and suggest that age at maturity is possibly >12 years. Most model parameter estimates for length-at-birth (L0) and asymptotic length (L∞) were biologically plausible. The Gompertz growth function, applied through a Bayesian hierarchical approach to back-calculated data, provided the best fitting and most biologically appropriate length-at-age parameters: L∞ = 229.5 cm TL ± (14.6 SE), gGom = 0.16 yr−1 ± (0.01 SE), and L0 = 58.2 cm TL ± (1.4 SE). The results presented here are the first study to apply Bayesian methods to back-calculated length-at-age data while accounting for repeated measures.

Identification of pesticides and their transformation products in surface water and groundwater surrounding a closed bioethanol production facility using non-targeted analysis - Angela L. Batt; Laura D. Brunelle; Eva K. Stebel; Daniel D. Snow; Esra Mutlu; Antony J. Williams; Gregory Janesch; Caroline Tebes-Stevens; Troy M. Ferland; Shannon Bartelt-Hunt; Judy Wu-Smart (Environmental Pollution, 2025)

The Blue Carbon Cost Tool – understanding market potential and investment requirements for high-quality coastal wetland projects - Stefanie Simpson; Lindsey S. Smart; Emily Landis; Stephanie Van Laere; Abu S. M. G. Kibria; Olga Albot; Mark Beeston; Catherine E. Lovelock; Robert I. McDonald; Ryan P. Moyer; Thomas A. Worthington; Tania L. Maxwell; et al. (Frontiers in Marine Science, 2025)
Blue carbon ecosystems, such as mangroves, tidal marshes, and seagrasses, are important for climate mitigation. As carbon sinks, they often exhibit higher per hectare carbon storage capacity and sequestration rates than terrestrial systems. These ecosystems provide additional benefits, including enhancing water quality, sustaining biodiversity, and maintaining coastal resilience to climate change impacts. The widespread loss of blue carbon ecosystems due to anthropogenic activities can contribute to increasing carbon emissions globally. Monetizing blue carbon through carbon credits offers an avenue to generate revenue and incentivize conservation and restoration efforts. However, limited data on project costs and carbon benefits make prioritization of blue carbon projects challenging. To address these challenges, we have developed, in collaboration with blue carbon experts, the Blue Carbon Cost Tool. This is a user-friendly interface enabling comparison of three core market project components – 1) carbon credit estimation, 2) project cost estimation, and 3) a qualitative, non-economic feasibility assessment – to assess and compare potential for blue carbon projects. Tool simulations with data available from nine countries demonstrate (a) how factors such as country, ecosystem type and project scale drive variability, (b) the need for local or project-specific data to enhance accuracy and reduce uncertainty, particularly in tidal marsh and seagrass systems, and (c) that higher price tolerance or upfront capital is needed to bridge implementation and maintenance cost gaps. The Blue Carbon Cost Tool can aid project developers and investors to better understand market opportunity and the resources needed to develop high quality blue carbon market projects.

Forest Topsoil Organic Carbon Declines Under Ash Dieback - Fiona M. Seaton; David A. Robinson; Claire M. Wood; Clare M. H. Benskin; Rebecca L. Rowe; Karen Hornigold; Keith J. Kirby; Chris Nichols; Simon M. Smart (Global Change Biology, 2025)
Tree diseases are increasingly affecting woodland ecosystems across the world. However, the impact of these diseases upon the soil, and in particular soil carbon, is still poorly understood. Here we present the results of a field survey of ~100 woodlands across Great Britain measured in 1971, 2001 and 2022 and evaluate the fifty‐year trend in topsoil (0–15 cm) carbon based upon measurements of soil organic matter (SOM) and the impact of Hymenoscyphus fraxineus (ash dieback). To better represent the full SOM distribution, including the extremely high SOM measurements, we adopt a Beta mixture modelling approach within a Bayesian framework. Across all woodlands, comprising ~1,500 plots per survey, average SOM remained constant across the fifty‐year time series. However, the 311 plots with ash dieback had lower SOM in the most recent survey compared to the 328 plots with ash trees present but no dieback recorded, due to a slight decline in SOM under ash dieback. This resulted in plots with ash dieback having a modelled mean SOM of 12.2% compared to 13.4% in plots without ash dieback, a difference of 1.23 percentage points (95% CI 0.25–2.21). Ash dieback was more likely to be recorded in plots that had higher soil pH pre‐ash dieback invasion, but the decline in SOM under ash dieback was not explained by changes in soil pH or changes in the ground flora composition. Converting our results to soil C and extrapolating for broadleaved woodland across the entirety of Great Britain, the total amount of topsoil carbon lost to date due to ash dieback could be 6 MtCO 2 (± 4 s.d.). Our results show the importance of understanding the impacts of tree disease when considering current and future woodland carbon dynamics.

Understanding genetic architecture overcomes tradeoffs between seed quality and insect resistance - Joseph R. White; James P. McNellie; Kyle G. Keepers; Brian C. Smart; Zoe M. Portlas; Zach E. Marcus; Nolan C. Kane; Jarrad R. Prasifka; Brent S. Hulke (Theoretical and Applied Genetics, 2025)

Distribution, drivers, and community perceptions of recent mass mangrove dieback in Maldives - S. Sreelekshmi; B. Aneesh; S. Bijoy Nandan; Aishath Farhath Ali; Mohammad Saddam Hussain; K. B. Smart; P. Hari Praved; M. Harikrishnan; Girish Gopinath; AL Achu; S. Vishnu Narayanan Nampoothiri; E. H. Aravind; et al. (Regional Environmental Change, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Probing ligands to reaction centers to limit the photocycle in photosynthetic bacterium Rubrivivax gelatinosus - M. Kis; J.L. Smart; P. Maróti (Journal of Photochemistry and Photobiology B: Biology, 2024)

Approaching the challenge of multi-phase, multi-hazard volcanic impact assessment through the lens of systemic risk: application to Taranaki Mounga - Alana M. Weir; Thomas M. Wilson; Mark S. Bebbington; Sarah Beaven; Teresa Gordon; Craig Campbell-Smart; Stuart Mead; James H. Williams; Roger Fairclough (Natural Hazards, 2024)
Effective volcanic impact and risk assessment underpins effective volcanic disaster risk management. Yet contemporary volcanic risk assessments face a number of challenges, including delineating hazard and impact sequences, and identifying and quantifying systemic risks. A more holistic approach to impact assessment is required, which incorporates the complex, multi-hazard nature of volcanic eruptions and the dynamic nature of vulnerability before, during and after a volcanic event. Addressing this need requires a multidisciplinary, integrated approach, involving scientists and stakeholders to co-develop decision-support tools that are scientifically credible and operationally relevant to provide a foundation for robust, evidence-based risk reduction decisions. This study presents a dynamic, longitudinal impact assessment framework for multi-phase, multi-hazard volcanic events and applies the framework to interdependent critical infrastructure networks in the Taranaki region of Aotearoa New Zealand, where Taranaki Mounga volcano has a high likelihood of producing a multi-phase explosive eruption within the next 50 years. In the framework, multi-phase scenarios temporally alternate multi-hazard footprints with risk reduction opportunities. Thus, direct and cascading impacts and any risk management actions carry through to the next phase of activity. The framework forms a testbed for more targeted mitigation and response planning and allows the investigation of optimal intervention timing for mitigation strategies during an evolving eruption. Using ‘risk management’ scenarios, we find the timing of mitigation intervention to be crucial in reducing disaster losses associated with volcanic activity. This is particularly apparent in indirect, systemic losses that cascade from direct damage to infrastructure assets. This novel, dynamic impact assessment approach addresses the increasing end-user need for impact-based decision-support tools that inform robust response and resilience planning.

Wilder rangelands as a natural climate opportunity: Linking climate action to biodiversity conservation and social transformation - Lavhelesani D. Simba; Mariska te Beest; Heidi-Jayne Hawkins; Keith W. Larson; Anthony R. Palmer; Camilla Sandström; Kathleen G. Smart; Graham I. H. Kerley; Joris P. G. M. Cromsigt (Ambio, 2024)
Rangelands face threats from climate and land-use change, including inappropriate climate change mitigation initiatives such as tree planting in grassy ecosystems. The marginalization and impoverishment of rangeland communities and their indigenous knowledge systems, and the loss of biodiversity and ecosystem services, are additional major challenges. To address these issues, we propose the wilder rangelands integrated framework, co-developed by South African and European scientists from diverse disciplines, as an opportunity to address the climate, livelihood, and biodiversity challenges in the world’s rangelands. More specifically, we present a Theory of Change to guide the design, monitoring, and evaluation of wilder rangelands. Through this, we aim to promote rangeland restoration, where local communities collaborate with regional and international actors to co-create new rangeland use models that simultaneously mitigate the impacts of climate change, restore biodiversity, and improve both ecosystem functioning and livelihoods.

Elevated CO 2 interacts with nutrient inputs to restructure plant communities in phosphorus‐limited grasslands - Christopher R. Taylor; Luke C. England; J. Ben Keane; Jessica A. C. Davies; Jonathan R. Leake; Iain P. Hartley; Simon M. Smart; Victoria Janes‐Bassett; Gareth K. Phoenix (Global Change Biology, 2024)
Globally pervasive increases in atmospheric CO 2 and nitrogen (N) deposition could have substantial effects on plant communities, either directly or mediated by their interactions with soil nutrient limitation. While the direct consequences of N enrichment on plant communities are well documented, potential interactions with rising CO 2 and globally widespread phosphorus (P) limitation remain poorly understood. We investigated the consequences of simultaneous elevated CO 2 (eCO 2 ) and N and P additions on grassland biodiversity, community and functional composition in P‐limited grasslands. We exposed soil‐turf monoliths from limestone and acidic grasslands that have received >25 years of N additions (3.5 and 14 g m −2 year −1 ) and 11 (limestone) or 25 (acidic) years of P additions (3.5 g m −2 year −1 ) to eCO 2 (600 ppm) for 3 years. Across both grasslands, eCO 2 , N and P additions significantly changed community composition. Limestone communities were more responsive to eCO 2 and saw significant functional shifts resulting from eCO 2 –nutrient interactions. Here, legume cover tripled in response to combined eCO 2 and P additions, and combined eCO 2 and N treatments shifted functional dominance from grasses to sedges. We suggest that eCO 2 may disproportionately benefit P acquisition by sedges by subsidising the carbon cost of locally intense root exudation at the expense of co‐occurring grasses. In contrast, the functional composition of the acidic grassland was insensitive to eCO 2 and its interactions with nutrient additions. Greater diversity of P‐acquisition strategies in the limestone grassland, combined with a more functionally even and diverse community, may contribute to the stronger responses compared to the acidic grassland. Our work suggests we may see large changes in the composition and biodiversity of P‐limited grasslands in response to eCO 2 and its interactions with nutrient loading, particularly where these contain a high diversity of P‐acquisition strategies or developmentally young soils with sufficient bioavailable mineral P.

Combining multiple investigative approaches to unravel functional responses to global change in the understorey of temperate forests - Dries Landuyt; Michael P. Perring; Haben Blondeel; Emiel De Lombaerde; Leen Depauw; Eline Lorer; Sybryn L. Maes; Lander Baeten; Laurent Bergès; Markus Bernhardt‐Römermann; Guntis Brūmelis; Jörg Brunet; et al. (Global Change Biology, 2024)
Plant communities are being exposed to changing environmental conditions all around the globe, leading to alterations in plant diversity, community composition, and ecosystem functioning. For herbaceous understorey communities in temperate forests, responses to global change are postulated to be complex, due to the presence of a tree layer that modulates understorey responses to external pressures such as climate change and changes in atmospheric nitrogen deposition rates. Multiple investigative approaches have been put forward as tools to detect, quantify and predict understorey responses to these global‐change drivers, including, among others, distributed resurvey studies and manipulative experiments. These investigative approaches are generally designed and reported upon in isolation, while integration across investigative approaches is rarely considered. In this study, we integrate three investigative approaches (two complementary resurvey approaches and one experimental approach) to investigate how climate warming and changes in nitrogen deposition affect the functional composition of the understorey and how functional responses in the understorey are modulated by canopy disturbance, that is, changes in overstorey canopy openness over time. Our resurvey data reveal that most changes in understorey functional characteristics represent responses to changes in canopy openness with shifts in macroclimate temperature and aerial nitrogen deposition playing secondary roles. Contrary to expectations, we found little evidence that these drivers interact. In addition, experimental findings deviated from the observational findings, suggesting that the forces driving understorey change at the regional scale differ from those driving change at the forest floor (i.e., the experimental treatments). Our study demonstrates that different approaches need to be integrated to acquire a full picture of how understorey communities respond to global change.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

P16-42: An in vitro toxicological assessment of two electronic cigarettes with differing heating techniologies:e-liquid to aerosolisation - E. Bishop; F. Miazzi; S. Bozhilova; N. East; R. Evans; D. Smart; D. Breheny; M. Gaca; D. Thorne (Toxicology Letters, 2023)

Landuse, landcover change dynamics and flooding in the lower Niger basin Onitsha, South Eastern Nigeria - Ezebube M. Nkiruka; Ani D. Chinedu; Uchegbu N. Smart (Land Use Policy, 2023)

Enzymatic degradation of carbonaceous matter in contrasting South African refractory gold ores using cell-free spent medium from Phanerochaete chrysosporium - Kojo T. Konadu; Didi X. Makaula; Mariette Smart; Cindy; Diego M. Mendoza; Elaine Opitz; Susan T.L. Harrison; Keiko Sasaki (Hydrometallurgy, 2023)

Ecosystem services in connected catchment to coast ecosystems: Monitoring to detect emerging trends - Christopher J. Brown; Chantal Saint Ange; Rod M. Connolly; Syezlin Hasan; Sue Jackson; Joseph M. McMahon; James C.R. Smart (Science of The Total Environment, 2023)

Resilience of ecosystem service delivery in grasslands in response to single and compound extreme weather events - Rosalind J. Dodd; David R. Chadwick; Paul W. Hill; Felicity Hayes; Antonio R. Sánchez-Rodríguez; Dylan Gwynn-Jones; Simon M. Smart; Davey L. Jones (Science of The Total Environment, 2023)

Influence of vegetation type and climatological conditions on evapotranspiration from extensive green roofs - Denis M. O'Carroll; Maria Eloisa Sia; Maja Staniec; James A. Voogt; Jeremy T. Lundholm; Charles C. Smart; Clare E. Robinson (Journal of Hydrology, 2023)

Estimating rock mechanical properties from microrebound measurements - Kevin J. Smart; David A. Ferrill; Caroline A. McKeighan; Frederick M. Chester (Engineering Geology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Identifying and mitigating risks to completion of small grant climate change adaptation projects: evidence from the Pacific - Syezlin Hasan; Christopher M. Fleming; James C. R. Smart; Andrew J. Buckwell; Maja Vinde Folkersen; Brendan Mackey (Regional Environmental Change, 2021)

Low accuracy of self-reported family history of melanoma in high-risk patients - Nicholas D. Flint; Michael D. Bishop; Tristan C. Smart; Jennifer L. Strunck; Kenneth M. Boucher; Douglas Grossman; Aaron M. Secrest (Familial Cancer, 2021)

Neuropsychological Impact of Trauma-Related Mental Illnesses: A Systematic Review of Clinically Meaningful Results - Kristen Silveira; Mauricio A. Garcia-Barrera; Colette M. Smart (Neuropsychology Review, 2020)

Zones of influence for soil organic matter dynamics: A conceptual framework for data and models - Claudia Cagnarini; Eleanor Blyth; Bridget A. Emmett; Chris D. Evans; Robert I. Griffiths; Aidan Keith; Laurence Jones; Inma Lebron; Niall P. McNamara; Jeremy Puissant; Sabine Reinsch; David A. Robinson; et al. (Global Change Biology, 2019)
Soil organic matter (SOM) is an indicator of sustainable land management as stated in the global indicator framework of the United Nations Sustainable Development Goals (SDG Indicator 15.3.1). Improved forecasting of future changes in SOM is needed to support the development of more sustainable land management under a changing climate. Current models fail to reproduce historical trends in SOM both within and during transition between ecosystems. More realistic spatio‐temporal SOM dynamics require inclusion of the recent paradigm shift from SOM recalcitrance as an ‘intrinsic property’ to SOM persistence as an ‘ecosystem interaction’. We present a soil profile, or pedon‐explicit, ecosystem‐scale framework for data and models of SOM distribution and dynamics which can better represent land use transitions. Ecosystem‐scale drivers are integrated with pedon‐scale processes in two zones of influence. In the upper vegetation zone, SOM is affected primarily by plant inputs (above‐ and belowground), climate, microbial activity and physical aggregation and is prone to destabilization. In the lower mineral matrix zone, SOM inputs from the vegetation zone are controlled primarily by mineral phase and chemical interactions, resulting in more favourable conditions for SOM persistence. Vegetation zone boundary conditions vary spatially at landscape scales (vegetation cover) and temporally at decadal scales (climate). Mineral matrix zone boundary conditions vary spatially at landscape scales (geology, topography) but change only slowly. The thicknesses of the two zones and their transport connectivity are dynamic and affected by plant cover, land use practices, climate and feedbacks from current SOM stock in each layer. Using this framework, we identify several areas where greater knowledge is needed to advance the emerging paradigm of SOM dynamics—improved representation of plant‐derived carbon inputs, contributions of soil biota to SOM storage and effect of dynamic soil structure on SOM storage—and how this can be combined with robust and efficient soil monitoring.

Model‐based hypervolumes for complex ecological data - Susan G. Jarvis; Peter A. Henrys; Aidan M. Keith; Ellie Mackay; Susan E. Ward; Simon M. Smart (Ecology, 2019)
Developing a holistic understanding of the ecosystem impacts of global change requires methods that can quantify the interactions among multiple response variables. One approach is to generate high dimensional spaces, or hypervolumes, to answer ecological questions in a multivariate context. A range of statistical methods has been applied to construct hypervolumes but have not yet been applied in the context of ecological data sets with spatial or temporal structure, for example, where the data are nested or demonstrate temporal autocorrelation. We outline an approach to account for data structure in quantifying hypervolumes based on the multivariate normal distribution by including random effects. Using simulated data, we show that failing to account for structure in data can lead to biased estimates of hypervolume properties in certain contexts. We then illustrate the utility of these “model‐based hypervolumes” in providing new insights into a case study of afforestation effects on ecosystem properties where the data has a nested structure. We demonstrate that the model‐based generalization allows hypervolumes to be applied to a wide range of ecological data sets and questions.

Characterization of a large sex determination region in Salix purpurea L. (Salicaceae) - Ran Zhou; David Macaya-Sanz; Eli Rodgers-Melnick; Craig H. Carlson; Fred E. Gouker; Luke M. Evans; Jeremy Schmutz; Jerry W. Jenkins; Juying Yan; Gerald A. Tuskan; Lawrence B. Smart; Stephen P. DiFazio (Molecular Genetics and Genomics, 2018)

Leveraging Big Data Towards Functionally-Based, Catchment Scale Restoration Prioritization - John P. Lovette; Jonathan M. Duncan; Lindsey S. Smart; John P. Fay; Lydia P. Olander; Dean L. Urban; Nancy Daly; Jamie Blackwell; Anne B. Hoos; Ana María García; Lawrence E. Band (Environmental Management, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Influence of fascicle length on twitch potentiation of the medial gastrocnemius across three ankle angles - Samantha L. Kuzyk; Rowan R. Smart; Carey L. Simpson; Andrey Fedorov; Jennifer M. Jakobi (European Journal of Applied Physiology, 2018)

Methane and carbon dioxide fluxes from open and blocked ditches in a blanket bog - Sophie M. Green; Andy J. Baird; Chris D. Evans; Mike Peacock; Joseph Holden; Pippa J. Chapman; Richard P. Smart (Plant and Soil, 2018)

Clarifying the key biodiversity areas partnership and programme - Simon N. Stuart; Thomas M. Brooks; Stuart H. M. Butchart; Wendy Elliott; Melanie Heath; Dieter Hoffmann; Leslie Honey; Irina Kostadinova; Penny Langhammer; Olivier Langrand; Susan Lieberman; Daniel Marnewick; et al. (Biodiversity and Conservation, 2018)

Non-Pharmacologic Interventions for Older Adults with Subjective Cognitive Decline: Systematic Review, Meta-Analysis, and Preliminary Recommendations - Colette M. Smart; Justin E. Karr; Corson N. Areshenkoff; Laura A. Rabin; Carol Hudon; Nicola Gates; Jordan I. Ali; Eider M. Arenaza-Urquijo; Rachel F. Buckley; Gael Chetelat; Harald Hampel; Frank Jessen; et al. (Neuropsychology Review, 2017)

Resistin and NGAL are associated with inflammatory response, endothelial activation and clinical outcomes in sepsis - Stephen P. J. Macdonald; Erika Bosio; Claire Neil; Glenn Arendts; Sally Burrows; Lisa Smart; Simon G. A. Brown; Daniel M. Fatovich (Inflammation Research, 2017)

Update of the activity of telavancin against a global collection of Staphylococcus aureus causing bacteremia, including endocarditis (2011–2014) - R. E. Mendes; H. S. Sader; J. I. Smart; M. Castanheira; R. K. Flamm (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

The impact of changing climate on perennial crops: the case of tea production in Sri Lanka - R. P. Dayani Gunathilaka; James C. R. Smart; Christopher M. Fleming (Climatic Change, 2017)

Electrophysiological and behavioral responses of female African rice gall midge, Orseolia oryzivora Harris and Gagné, to host plant volatiles - Emmanuel O. Ogah; Lesley E. Smart; Christine M. Woodcock; John C. Caulfield; Michael A. Birkett; John A. Pickett; Francis E. Nwilene; Toby J. Bruce (Journal of Chemical Ecology, 2017)

Duration of fascicle shortening is affected by muscle architecture and sex - C. L. Simpson; S. Arefin; R. R. Smart; B. Harwood; Jennifer M. Jakobi (European Journal of Applied Physiology, 2016)

Climate change impacts and adaptive strategies: lessons from the grapevine - Jonathan R. Mosedale; Kirsten E. Abernethy; Richard E. Smart; Robert J. Wilson; Ilya M. D. Maclean (Global Change Biology, 2016)
The cultivation of grapevines for winemaking, known as viticulture, is widely cited as a climate‐sensitive agricultural system that has been used as an indicator of both historic and contemporary climate change. Numerous studies have questioned the viability of major viticulture regions under future climate projections. We review the methods used to study the impacts of climate change on viticulture in the light of what is known about the effects of climate and weather on the yields and quality of vineyard harvests. Many potential impacts of climate change on viticulture, particularly those associated with a change in climate variability or seasonal weather patterns, are rarely captured. Key biophysical characteristics of viticulture are often unaccounted for, including the variability of grapevine phenology and the exploitation of microclimatic niches that permit successful cultivation under suboptimal macroclimatic conditions. We consider how these same biophysical characteristics permit a variety of strategies by which viticulture can adapt to changing climatic conditions. The ability to realize these strategies, however, is affected by uneven exposure to risks across the winemaking sector, and the evolving capacity for decision‐making within and across organizational boundaries. The role grape provenance plays in shaping perceptions of wine value and quality illustrates how conflicts of interest influence decisions about adaptive strategies within the industry. We conclude by considering what lessons can be taken from viticulture for studies of climate change impacts and the capacity for adaptation in other agricultural and natural systems.

Legacy effects of grassland management on soil carbon to depth - Susan E. Ward; Simon M. Smart; Helen Quirk; Jerry R. B. Tallowin; Simon R. Mortimer; Robert S. Shiel; Andrew Wilby; Richard D. Bardgett (Global Change Biology, 2016)
The importance of managing land to optimize carbon sequestration for climate change mitigation is widely recognized, with grasslands being identified as having the potential to sequester additional carbon. However, most soil carbon inventories only consider surface soils, and most large‐scale surveys group ecosystems into broad habitats without considering management intensity. Consequently, little is known about the quantity of deep soil carbon and its sensitivity to management. From a nationwide survey of grassland soils to 1 m depth, we show that carbon in grassland soils is vulnerable to management and that these management effects can be detected to considerable depth down the soil profile, albeit at decreasing significance with depth. Carbon concentrations in soil decreased as management intensity increased, but greatest soil carbon stocks (accounting for bulk density differences), were at intermediate levels of management. Our study also highlights the considerable amounts of carbon in subsurface soil below 30 cm, which is missed by standard carbon inventories. We estimate grassland soil carbon in Great Britain to be 2097 Tg C to a depth of 1 m, with ~60% of this carbon being below 30 cm. Total stocks of soil carbon (t ha −1 ) to 1 m depth were 10.7% greater at intermediate relative to intensive management, which equates to 10.1 t ha −1 in surface soils (0–30 cm), and 13.7 t ha −1 in soils from 30 to 100 cm depth. Our findings highlight the existence of substantial carbon stocks at depth in grassland soils that are sensitive to management. This is of high relevance globally, given the extent of land cover and large stocks of carbon held in temperate managed grasslands. Our findings have implications for the future management of grasslands for carbon storage and climate mitigation, and for global carbon models which do not currently account for changes in soil carbon to depth with management.

RHEB1 expression in embryonic and postnatal mouse - Qi Tian; James L. Smart; Joachim H. Clement; Yingming Wang; Alex Derkatch; Harald Schubert; Michael V. Danilchik; Daniel L. Marks; Lev M. Fedorov (Histochemistry and Cell Biology, 2016)

Empirical realised niche models for British coastal plant species - Susan G. Jarvis; Edwin C. Rowe; Peter A. Henrys; Simon M. Smart; Laurence Jones; Angus Garbutt (Journal of Coastal Conservation, 2016)

Estimating tsunami run-up - G. M. Smart; K. H. M. Crowley; E. M. Lane (Natural Hazards, 2016)

Multi-decadal decline in reef fish abundance and species richness in the southeast USA assessed by standardized trap catches - Nathan M. Bacheler; Tracey I. Smart (Marine Biology, 2016)

Chemical defense lowers plant competitiveness - Daniel J. Ballhorn; Adrienne L. Godschalx; Savannah M. Smart; Stefanie Kautz; Martin Schädler (Oecologia, 2014)

A functional classification of herbaceous hedgerow vegetation for setting restoration objectives - C. N. R. Critchley; L. A. Wilson; A. C. Mole; L. R. Norton; S. M. Smart (Biodiversity and Conservation, 2013)

Estimation of actual evapotranspiration in winegrape vineyards located on hillside terrain using surface renewal analysis - T. M. Shapland; R. L. Snyder; D. R. Smart; L. E. Williams (Irrigation Science, 2012)

Environmental cues and seasonal reproduction in a temperate estuary: a case study of Owenia collaris (Annelida: Polychaeta, Oweniidae) - Tracey I. Smart; Craig M. Young; Richard B. Emlet (Marine Ecology, 2012)
Coordination of gametogenesis and spawning during restricted breeding seasons increases availability of mates, fertilization rates, and often success of offspring. Orton’s Rule predicts water temperature as the dominant environmental cue for gametogenesis or spawning in temperate invertebrates. Crisp’s Rule predicts that species producing planktotrophic larvae will time their reproduction to ensure optimal nutrition for the larvae. Owenia collaris (Annelida: Oweniidae) is a temperate polychaete that produces planktotrophic larvae that remain in the water column for several weeks. Reproductive phenology and its relationship to the environment were investigated in an estuarine population of O. collaris using field and laboratory studies. Owenia collaris produced mature gametes between March and September each year during the productive season between the spring and fall transitions when day lengths were 12 h or more, alkalinity was 8.1 or higher, and temperature was 11 °C or higher. Gamete production was not related to seasonal changes in salinity or benthic phytoplankton concentrations and gametes were present prior to the spring phytoplankton bloom. In laboratory experiments, production of gametes was influenced somewhat by manipulating day lengths but not adult food. The association with predictable and stable environmental cycles (day length) and a broad spawning season suggest that this species is unlikely to mis‐match with larval food availability which would lead to reduced availability of recruits in any given year, supporting Crisp’s Rule. Our data do not support the hypothesis that reproductive timing in this species is driven by access to excess energy required by adults to initiate the production of gametes. Our data also do not support Orton’s premise that temperature is the primary controlling factor of reproduction in this temperate marine invertebrate.

Production of liver preneoplasia and gallbladder agenesis in turkey fetuses administered diethylnitrosamine - Gary M. Williams; Klaus D. Brunnemann; Michael J. Iatropoulos; Daniel J. Smart; Harald G. Enzmann (Archives of Toxicology, 2011)

Interpreting spatial language in image captions - Mark M. Hall; Philip D. Smart; Christopher B. Jones (Cognitive Processing, 2011)

Aliens or natives: who are the ‘thugs’ in British woods? - R. H. Marrs; M. G. Le Duc; S. M. Smart; K. J. Kirby; R. G. H. Bunce; P. M. Corney (Kew Bulletin, 2010)

Nitrogen deposition causes widespread loss of species richness in British habitats - LINDSAY C. MASKELL; SIMON M. SMART; JAMES M. BULLOCK; KEN THOMPSON; CARLY J. STEVENS (Global Change Biology, 2010)
We use national scale data to test the hypothesis that nitrogen (N) deposition is strongly negatively correlated with plant species richness in a wide range of ecosystem types. Vegetation plots from a national ecological surveillance programme were drawn from heathland, acid, calcareous and mesotrophic grassland habitats. Mean species number and mean plant traits were calculated for each plot and related to atmospheric N deposition. There was a significant reduction in species richness with N deposition in acid grassland and heathland even after fitting covarying factors. In acid grassland and heathland, evidence from trait changes suggested that acidification rather than increased fertility was responsible for species loss. In contrast, calcareous grassland showed evidence of eutrophication in response to increasing N deposition. Loss of species richness from chronic N deposition is apparent in infertile grasslands and heathland. Mechanisms associated with loss of species richness differ between habitats so mitigation of N deposition should be targeted to habitat type.

A mathematical model to study the effect of hepatitis B virus vaccine and antivirus treatment among the Canadian Inuit population - C. O’Leary; Z. Hong; F. Zhang; M. Dawood; G. Smart; K. Kaita; J. Wu (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Spawning and development in Osedax boneworms (Siboglinidae, Annelida) - Greg W. Rouse; Nerida G. Wilson; Shana K. Goffredi; Shannon B. Johnson; Tracey Smart; Chad Widmer; Craig M. Young; Robert C. Vrijenhoek (Marine Biology, 2009)

Characterization and mapping of R Pi-ber , a novel potato late blight resistance gene from Solanum berthaultii - G. M. Rauscher; C. D. Smart; I. Simko; M. Bonierbale; H. Mayton; A. Greenland; W. E. Fry (Theoretical and Applied Genetics, 2006)

Epidemiological study of hepatitis B virus infection in Manitoba, Canada, 1992–2003 - Z. Hong; G. Smart; G. Zaniewski; H. Wu; J. Wu; N. Goedhuis; A. Giulivi; K. Kaita; M. Dawood (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Method for the generation and cultivation of functional three-dimensional mammary constructs without exogenous extracellular matrix - N. E. Timmins; F. J. Harding; C. Smart; M. A. Brown; L. K. Nielsen (Cell and Tissue Research, 2005)

Seedling sulfide sensitivity among plant species colonizing Phragmites-infested wetlands - Denise M. Seliskar; Kristen E. Smart; Bryan T. Higashikubo; John L. Gallagher (Wetlands, 2004)

Orientation and Feeding Responses of the Pollen Beetle, Meligethes aeneus, to Candytuft, Iberis amara - Elspeth Bartlet; Margaret M. Blight; John A. Pickett; Lesley E. Smart; Grenville Turner; Christine M. Woodcock (Journal of Chemical Ecology, 2004)

Locating eutrophication effects across British vegetation between 1990 and 1998 - Simon M. Smart; Joanne C. Robertson; Eleanor J. Shield; Helena M. Van De Poll (Global Change Biology, 2003)
Large‐scale ecological surveillance data were analysed to determine the locations of apparent eutrophication effects across common British vegetation types between 1990 and 1998. Plant species composition was recorded from a total of 9514 fixed plots located in a stratified, random sample of 501 1 km squares across Britain. Changes in plant species composition along a gradient of substrate fertility were inferred from statistical tests of change in mean Ellenberg fertility value calculated for each fixed plot. Plots were grouped by eight vegetation types, five landscape features (hedges, road verges, watercourse banks, small biotopes, larger units in fields and unenclosed land) and six environmental zones. Tests of change in mean Ellenberg value were carried out on all combinations of these strata. Decision tree modelling was used to identify groups of test outcomes sharing the same direction of change and where each group was defined by a minimum number of strata. Post hoc power analysis was used to select statistically non‐significant test outcomes that could be used to infer stability in the sampled sub‐population. Out of a total of 142 tests of change in fertility value, 67% were increases, 8% were reductions and 25% indicated stability. The best overall predictor of increases in fertility value, and therefore of shifts in favour of plants suited to higher substrate fertility, was vegetation type. Irrespective of landscape feature and environmental zone, increased means were associated with infertile grasslands, moorland, upland woodlands and heath/bog. Already highly fertile grasslands and woodland assemblages in lowland Britain remained largely stable. The small number of decreasing test outcomes were associated with arable land in Scotland, Wales and western England. These patterns of change are hypothesized to reflect pervasive land‐use drivers combined with the inherent responsiveness of the vegetation.

Dormant Buds and Adventitious Root Formation by Vitis and Other Woody Plants - David R. Smart; Laszlo Kocsis; M. Andrew Walker; Christine Stockert (Journal of Plant Growth Regulation, 2002)

Population fluctuations and their causes in the African Fish Eagle, (Haliaeetus vocifer (Daudin)) at Lake Naivasha, Kenya - David M. Harper; Maureen M. Harper; Munir A. Virani; Andrew Smart; R. Brooks Childress; Rachel Adatia; Ian Henderson; Bernard Chege (Hydrobiologia, 2002)

Distribution and abundance of the Louisiana red swamp crayfish Procambarus clarkii Girard at Lake Naivasha, Kenya between 1987 and 1999 - David M. Harper; Andrew C. Smart; Stephanie Coley; Sophie Schmitz; Anne-Christine Gouder de Beauregard; Rick North; Chris Adams; Paul Obade; Mbogo Kamau (Hydrobiologia, 2002)

Feeding of the exotic Louisiana red swamp crayfish, Procambarus clarkii (Crustacea, Decapoda), in an African tropical lake: Lake Naivasha, Kenya - Andrew C. Smart; David M. Harper; François Malaisse; Sophie Schmitz; Stephanie Coley; Anne-Christine Gouder de Beauregard (Hydrobiologia, 2002)

Ecological assessment of vegetation from a nature reserve using regional reference data and indicator scores - Simon M. Smart (Biodiversity and Conservation, 2000)

Response of the Pollen Beetle, Meligethes aeneus, to Traps Baited with Volatiles from Oilseed Rape, Brassica napus - Lesley E. Smart; Margaret M. Blight (Journal of Chemical Ecology, 2000)

An Alu -mediated large deletion of the FUT2 gene in individuals with the ABO-Bombay phenotype - Y. Koda; M. Soejima; P.H. Johnson; E. Smart; H. Kimura (Human Genetics, 2000)

An Alu-mediated large deletion of the FUT2 gene in individuals with the ABO-Bombay phenotype - Y. Koda; M. Soejima; P.H. Johnson; E. Smart; H. Kimura (Human Genetics, 2000)

Isolation of RNA and Protein from Guard Cells of Nicotiana glauca - Lawrence B. Smart; Nicole M. Nall; Alan B. Bennett (Plant Molecular Biology Reporter, 1999)

Influence of Visual Cues and Isothiocyanate Lures on Capture of the Pollen Beetle, Meligethes aeneus in Field Traps - Margaret M. Blight; Lesley E. Smart (Journal of Chemical Ecology, 1999)

Life after lakes: the ecology and management of the water distribution network - Andrew C. Smart; David M. Harper (Hydrobiologia, 1999)

Effects of sulfate on cadmium uptake by Swiss chard: I. Effects of complexation and calcium competition in nutrient solutions - M. J. McLaughlin; S. J. Andrew; M.K. Smart; E. Smolders (Plant and Soil, 1998)

Field Discrimination of Oilseed Rape, Brassica napus Volatiles by Cabbage Seed Weevil, Ceutorhynchus assimilis - Lesley E. Smart; Margaret M. Blight (Journal of Chemical Ecology, 1997)

Effect of Visual Cues and a Mixture of Isothiocyanates on Trap Capture of Cabbage Seed Weevil, Ceutorhynchus assimilis - Lesley E. Smart; Margaret M. Blight; Alastair J. Hick (Journal of Chemical Ecology, 1997)

Utilisation of Wild Gramineous Plants for Management of Cereal Stemborers in Africa - Z. R. Khan; P. Chiliswa; K. Ampong-Nyarko; L. E. Smart; A. Polaszek; J. Wandera; M. A. Mulaa (International Journal of Tropical Insect Science, 1997)

Field-scale biofiltration of gasoline vapors extracted from beneath a leaking underground storage tank - Eileen Maura Jutras; Cecil M. Smart; Richard Rupert; Ian L. Pepper; Raina M. Miller (Biodegradation, 1997)

Effect of phosphorus supply on periplasmic protein profiles in Rhizobia - J. B. Smart; M. J. Dilworth; A. D. Robson (Archives of Microbiology, 1984)

Effect of phosphorus supply on phosphate uptake and alkaline phosphatase activity in Rhizobia - J. B. Smart; M. J. Dilworth; A. D. Robson (Archives of Microbiology, 1984)

A continuous culture study of the phosphorus nutrition of Rhizobium trifollii WU95, Rhizobium NGR234 and Bradyrhizobium CB756 - J. B. Smart; A. D. Robson; M. J. Dilworth (Archives of Microbiology, 1984)